2018
DOI: 10.1044/2018_jslhr-h-17-0245
|View full text |Cite
|
Sign up to set email alerts
|

Memory Span for Spoken Digits in Adults With Cochlear Implants or Typical Hearing: Effects of Age and Identification Ability

Abstract: Digit span can be studied independently of perception in many adult CI users. For both CI listeners and listeners with NH, stimulus degradation does not appear to significantly affect memory span, unless an effect on simple identification is also present. Auditory degradation that may slow, but which does not ultimately prevent identification, appears to have negligible impact on short-term and working memory spans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Demands on short-term memory likely exacerbate the age confound between our NH and CI listeners. Future work could consider using fewer keywords and providing age-matched controls to this task (Cleary et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Demands on short-term memory likely exacerbate the age confound between our NH and CI listeners. Future work could consider using fewer keywords and providing age-matched controls to this task (Cleary et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies used digit span tasks to compare auditory working memory in which participants hear and recall a sequence of digits; the length of sequences increase as participants recall them correctly. Performances for CI users were reduced in Tao et al (2014) and Hamdy et al (2023) but similar between groups in Moberly et al (2017a) and Cleary et al (2018). The latter is possibly a result of each sequence length being presented twice allowing participants a chance to perform better on each sequence and therefore, resulting in no significant differences.…”
Section: Introductionmentioning
confidence: 87%
“…Direct comparisons between the current findings and previous literature are difficult because very few studies have directly compared CI users and TH listeners in auditory memory tasks and those that have, yielded inconsistent results. Moberly et al (2017a) and Cleary et al (2018) compared CI users and TH listeners on an auditory digit span test and showed no group differences for either forward or reverse digit spans. However, Tao et al (2014) compared CI users and TH listeners on a digit span test and found that only reverse digit span scores were lower in CI users compared to TH controls while forward digit span were comparable across groups.…”
Section: Online Tests and Survey Outcomes Between Groupsmentioning
confidence: 99%